2022
DOI: 10.1007/s00167-022-07077-1
|View full text |Cite
|
Sign up to set email alerts
|

Two-type classification system for femoral trochlear dysplasia in recurrent patellar instability based on three-dimensional morphology

Abstract: Purpose Radiographic and two-dimensional (2D) CT/MRI analysis of femoral trochlear dysplasia play a signiicant role in surgical decision-making for recurrent patellar instability. However, the three-dimensional morphology of dysplastic trochlea is rarely studied due to the limitations of conventional imaging modalities. This study aimed to (1) develop a 3D morphological classiication for trochlear dysplasia based on the concavity of the trochlear groove and ( 2) analyze the interrater reliability of the classi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
21
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 48 publications
0
21
0
Order By: Relevance
“…No additional studies were identified from reference lists, which left ten relevant studies for data extraction [4,6,22,30,31,39,41,54,58,65]. The second electronic search on 31 July 2023 yielded one additional study published after the first electronic search, which was added to the analysis [50] (Fig.…”
Section: Study Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…No additional studies were identified from reference lists, which left ten relevant studies for data extraction [4,6,22,30,31,39,41,54,58,65]. The second electronic search on 31 July 2023 yielded one additional study published after the first electronic search, which was added to the analysis [50] (Fig.…”
Section: Study Selectionmentioning
confidence: 99%
“…Yang et al [65] reported that intra-observer agreement was moderate to substantial when classifying dysplasia into four categories, but substantial to near perfect when classifying dysplasia into two categories using CT. Fuchs et al [31] reported that intra-observer agreement was moderate to substantial when classifying dysplasia into four categories, but fair to near perfect when classifying dysplasia into two categories using MRI.…”
Section: Intra-observer Repeatability Of the Dejour Classificationmentioning
confidence: 99%
“…Moreover, prior studies analyzing the data in human skeleton system [15][16][17][18][19] have con rmed that the measured data from 3D reconstruction measurement results are more consistent and accurate than that from 2D measures. Some morphological studies have reported racial and gender differences in sinus [8, [14][15][16]. One recent study showed that Chinese ES was about 16% wider than examples from another study [13].…”
Section: Introductionmentioning
confidence: 99%
“…3 The abnormal shape of a dysplastic trochlea has been described on axial imaging as a decreased slope of the medial or lateral condyle as well as a decreased depth of the trochlear floor and abnormalities in trochlear width. 2,8,14,15,26 Several studies 5,6,17,23 have assessed patients who sustained first-time patellar dislocations and identified trochlear dysplasia as a primary risk factor for recurrent instability. While the cause of patellar instability is multifactorial, Christensen et al 10 noted in a retrospective study of 584 patients that the presence of trochlear dysplasia was the primary risk factor (odds ratio, 18.1) for the recurrence of instability after a first-time patellar dislocation episode.…”
mentioning
confidence: 99%
“… 3 The abnormal shape of a dysplastic trochlea has been described on axial imaging as a decreased slope of the medial or lateral condyle as well as a decreased depth of the trochlear floor and abnormalities in trochlear width. 2 , 8 , 14 , 15 , 26 …”
mentioning
confidence: 99%